Chapter 3 Beyond Ring Composition A Comparison of Formal Features in Sūrat al- ʿAlaq (Q 96) and Bavli Bava Batra 8a* - Zellentin, Holger (Taylor & Francis, 2021)
In this chapter, the author discovers Michel Cuypers' pioneering application to the Qur'an of the Semitic rhetorical analysis of Roland Meynet. It takes the reader through the first 33 verses of Surat Maryam to show how a discourse grammar of the Qur'an functions. Both Surat al-'Alaq and the Talmudic story the people have analyzed, it is true, implement a teaching equally found in the Mishna, just as the Medinan Surat al-Ma idah will later explicitly quote a saying that is quite in line with another Mishnaic passage. This basic division of the surah (what the author henceforth calls the "traditional one") into two parts corresponds to the fact that are set apart by means of the repetition of initial words, which, crucially, also corresponds to the remaining shifts in rhyme scheme between all subunits. Finally, the chapter points out the fruits of identifying the discourse grammar of these two stories for interpreting the surah as a whole.